Increased number of cryptosporidiosis cases with travel history to Croatia might be related to swimming pools, Germany, 2023 - Schoeps, Anja; Röbl, Klara; Walter, Nicole; Neute, Andrea; Walter, Bernadette; Freudenau, Inga; Jurke, Annette; Klier, Christiane; Heinmüller, Petra; Saeed, Syamend; Metz, Jasmin; Wilking, Hendrik; et al. (Eurosurveillance, 2024)
In August and September 2023, an unusually high number of cryptosporidiosis cases identified by routine German surveillance had travelled to Croatia (n = 23). Nine cases had stayed in the same camping resort and seven further cases had stayed at other camping sites within 15 km. Based on our standardised questionnaires, the most likely source of infection was swimming pools (93%). Further environmental investigations on site might reveal potential common sources of contamination that could be targeted by control measures.
Gesehen am 25.09.2024